2015
DOI: 10.5817/cpr2015-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of freshwater autotrophs in selected wet places in northern coastal ecosystems of James Ross Island

Abstract: The authors thank to the infrastructure of the CzechPolar programme for providing facilities necessary for sample collection, their storage and handling before microscopic study. This research was also supported by the project of Masaryk University MUNI/A/1370/2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Bottoms of streams are rich in cyanobacterial and algal species (see e.g. Skácelová et al 2015). Several moss species form individual moss carpets, however Bryum pseudotriquetrum and Hypnum revolutum dominate the com-munity (see Fig.…”
Section: Location Of Moss-dominated Areasmentioning
confidence: 99%
“…Bottoms of streams are rich in cyanobacterial and algal species (see e.g. Skácelová et al 2015). Several moss species form individual moss carpets, however Bryum pseudotriquetrum and Hypnum revolutum dominate the com-munity (see Fig.…”
Section: Location Of Moss-dominated Areasmentioning
confidence: 99%
“…Based on the relative abundance data, the principal taxon was Luticola muticopsis, a cosmopolitan species, frequently reported from Antarctica and typically found in terrestrial habitats influenced by sea birds and sea sprays (Zidarova et al 2016). The dominant taxa are typical terrestrial species reported to be frequent also in microbial mat samples on JRI (Skácelová et al 2015) and soils, where Chattová et al (2016) found 86 diatom taxa. Such relatively high number of typical terrestrial species of diatoms found in the lichen samples is not surprising, considering the fact that the lichen microhabitat can be characterized by extreme environmental conditions, mainly by unstable moisture regime.…”
Section: Discussionmentioning
confidence: 92%
“…The collection site was a shallow stream passing through the vegetation oasis formed by numerous moss and lichen species (for details see e.g. Barták et al 2015). The site was located close to a seashore at the altitude of 5-8 m a.s.l.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, the northern part of James Ross Island is deglaciated and rich in terrestrial freshwater lakes (Nedbalová et al 2013), small-area ponds (Váczi et Barták 2011) and streams. All these ecosystems are inhabited by algae and cyanobacteria (see Skácelová et al 2015 for preliminary review).…”
Section: Methodsmentioning
confidence: 99%